Nutrition considerations for open-water swimming - Shaw, G.; Koivisto, A.; Gerrard, D.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Open-water swimming (OWS) is a rapidly developing discipline. Events of 5-25 km are featured at FINA World Championships, and the international circuit includes races of 5-88 km. The Olympic OWS event, introduced in 2008, is contested over 10 km. Differing venues present changing environmental conditions, including water and ambient temperatures, humidity, solar radiation, and unpredictable tides. Furthermore, the duration of most OWS events (1-6 hr) creates unique physiological challenges to thermoregulation, hydration status, and muscle fuel stores. Current nutrition recommendations for open-water training and competition are either an extension of recommendations from pool swimming or are extrapolated from other athletic populations with similar physiological requirements. Competition nutrition should focus on optimizing prerace hydration and glycogen stores. Although swimmers should rely on self-supplied fuel and fluid sources for shorter events, for races of 10 km or greater, fluid and fuel replacement can occur from feeding pontoons when tactically appropriate. Over the longer races, feeding pontoons should be used to achieve desirable targets of up to 90 g/ hr of carbohydrates from multitransportable sources. Exposure to variable water and ambient temperatures will play a significant role in determining race nutrition strategies. For example, in extreme environments, thermo- regulation may be assisted by manipulating the temperature of the ingested fluids. Swimmers are encouraged to work with nutrition experts to develop effective and efficient strategies that enhance performance through appropriate in-competition nutrition.